2020
DOI: 10.31234/osf.io/vazeh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interpersonal neural synchrony during father-child problem solving: An fNIRS hyperscanning study

Abstract: Interpersonal neural synchrony (INS) has been previously evidenced in mother-child interactions, yet findings concerning father-child interaction are wanting. The current experiment examined whether fathers and their 5- to 6-year-old children (N=66) synchronize their brain activity during a naturalistic interaction, and addressed paternal and child factors related to INS. Compared to individual problem-solving and rest, father-child dyads showed INS in dorsolateral prefrontal and temporo-parietal brain areas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…The present findings additionally dovetail with another recent observation from a study of the same sample of fathers; fathers participating in D-CARE additionally underwent an fNIRS hyperscanning protocol together with their 5-to-6 year old children to assess father-child interpersonal neural synchrony (Nguyen et al, 2020). Nguyen et al report that fathers with higher scores on the ROFQ-D showed a greater degree of interpersonal neural synchrony in bilateral dorsolateral prefrontal cortex and left temporo-parietal junction when engaging in cooperative problem-solving with their children.…”
Section: Hypothalamus Volume and Caregiving Style In Fatherssupporting
confidence: 88%
“…The present findings additionally dovetail with another recent observation from a study of the same sample of fathers; fathers participating in D-CARE additionally underwent an fNIRS hyperscanning protocol together with their 5-to-6 year old children to assess father-child interpersonal neural synchrony (Nguyen et al, 2020). Nguyen et al report that fathers with higher scores on the ROFQ-D showed a greater degree of interpersonal neural synchrony in bilateral dorsolateral prefrontal cortex and left temporo-parietal junction when engaging in cooperative problem-solving with their children.…”
Section: Hypothalamus Volume and Caregiving Style In Fatherssupporting
confidence: 88%
“…fNIRS was simultaneously measured in both participants in bilateral temporo-parietal junction (left hemisphere: Channel 9-12; right hemisphere: Channel 13-16) and dorsolateral prefrontal cortex (left hemisphere: Channel 1-4; right hemisphere: Channel 5-8). For a full description of the study design, please refer to [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…We also need to better understand differences in interpersonal neural synchrony patterns, such as across distinct brain regions, interaction partners, and age. For example, there is emerging evidence that patterns of interpersonal neural synchrony in parent-child dyads seem to diverge for mothers and fathers, with fathers showing a more anatomically localized synchrony pattern [25]. Mothers, on the other hand, seem to show a more anatomically widespread synchrony pattern in frontal and temporal brain areas [26,36].…”
Section: General Considerationsmentioning
confidence: 99%
“…In the same year, Nguyen et al (2020c) tried to extend such results to father-child social interactions. The authors observed neural synchronization between fathers and children's brains in bilateral dorsolateral prefrontal cortex and the left temporoparietal junction during cooperation.…”
Section: Cluster #1: "Neural Attunement"mentioning
confidence: 99%